Temporal and spatial investigation of maritime accidents in the strait of Istanbul in the perspective of navigational safety - Kodak, Gizem (Graduate School, 2022)
The Strait of Istanbul is located on the primary routes of international maritime transport. The strait, which is the second busiest waterway in the world with average of 50.000 ships per year, has four times more maritime traffic than the Panama Canal and three times more than the Suez Canal. When compared to its peer waterways the biggest threat in the Strait, the risk of accidents created by difficult navigational conditions. Some of the accidents that took place in the strait in the recent past have caused worldwide concern due to the environmental disaster they have caused. Considering that today, ships carrying dangerous goods serve at much larger capacities compared to the past, the maritime traffic in the region poses a risk both for the ships passing and for the city and people of Istanbul, which is densely populated on its shores. In this context, the development of solutions to reduce maritime accidents in the region plays a key role in strengthening navigational safety. In this study, the accidents that took place in the strait were discussed in terms of temporal/spatial and were examined simultaneously with the environmental factors affecting the navigational safety. For this purpose, hourly wind speed and wind direction data of Sarıyer and Atatürk meteorology stations located on the traffic route in the strait were obtained from the Turkish State Meteorological Service and wind dynamics affecting maritime traffic were examined. On the other hand, accidents also were evaluated in terms of the number of ships passing and the effect of maritime traffic on accidents were examined with the regression analysis. In this direction the monthly movement of international ship traffic in the strait was examined on a micro scale with the data of the Directorate General of Coastal Safety and accident rate per passing ship was calculated. In addition to dynamic factors such as wind speed, wind direction and traffic flow, another factor affecting the occurrence of accidents in the strait is the navigational regulations carried out in relation to the traffic order. In this context, the regulations for maritime traffic in the strait were examined chronologically and compared with the accident data. Thus, not only the effects of the regulations regarding navigational safety on the accidents were observed, but also the strengths and weaknesses of the developed solution proposals were revealed. The results of the study have shown that patrol tugs can be an effective solution to prevent accidents when the wind and current dynamics in the region and the spatial distribution of the accidents are evaluated together. In this direction, the response time of the proposed patrol tugboats to a possible accident was calculated and the response options were evaluated under two different scenarios as parallel to the current and antiparallel.
İstanbul Boğazı'ndaki deniz kazalarının seyir emniyeti perspektifinde zamansal ve mekansal olarak incelenmesi
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: maritime accidents; deniz kazaları; maritime transport; deniz taşımacılığı; Istanbul strait; İstanbul boğazı; maritime traffic; deniz trafiği